Measuring the natural interest rate for the Macedonian economy: A multi-model approach - Mite Miteski; Magdalena Petrovska; Artan Sulejmani (National Bank of the Republic of North Macedonia, 2023)
This paper identifies the natural interest rate for the Macedonian economy using quarterly data for 2001Q4-2019Q3. To this end, the estimation is made by using different types of models, such as the Holston, Laubach, and Williams model and the full-fledged country-specific structural MAKPAM model. The empirical results show that the natural rate of interest in the Macedonian economy has declined over time, which is similar to the findings for other countries. The decomposition of the natural rate suggests that the main driver for the decline is the slowdown of the Macedonian potential GDP growth in the period after the global economic crisis, although there are signs of its recovery at the end of the sample period. In addition, the results indicate that the monetary policy conditions in the Macedonian economy have been broadly accommodative from 2011Q4 onwards. The substantive conclusions are unchanged across the multiple models used in this study.
Keywords: C32; E43; E52; O40; 330; Natural interest rate; interest rate gap; Holston; Laubach; and Williams model; MAKPAM Model